Factors Influencing Patients’ Retention in HIV Chronic Care Clinics in Nakuru County, Kenya - Nura, Abagudo Qabalena; Mwaura-Tenambergen, Wanja; Muiruri, Lillian (International Journal of Professional Practice, 2024)
Human Immunodeficiency Virus /Acquired Immunodeficiency Syndrome (HIV/AIDS) has remained a threat to global public health. Despite the benefits of Antiretroviral Therapy in reducing mortality and morbidity, many people living with the HIV are not retained in chronic care clinics to control disease spread. Thus, rapid expansion of Antiretroviral Therapy (ART) programmes without understanding the service factors that shape the behaviours of HIV-positive people will undermine its effectiveness, waste precious resources, and result in the emergence of ART-resistant viruses. This study assessed health service delivery factors affecting HIV care retention in Nakuru County. A descriptive cross-sectional design was used for the study. The researcher investigated those who kept appointments and those who did not so as to understand their challenges. The target population comprised 2963 HIV-positive clients. The sample size, calculated using Krejcie and Morgan’s table, was 300. Simple random sampling was used to select those who honoured appointments, and appointment diaries were used to pick the defaulters. Caregivers helped in administering questionnaires to those who kept their appointments, while the defaulters were interviewed over the phone by the researcher. SPSS version 26 was used to analyse descriptive and inferential statistics such as mean and standard deviation. Logistic regression was used to identify factors influencing care retention. The findings revealed that health providers’ friendliness, quality of service, time taken at the facility, and the ease to secure off days at work were service delivery factors associated with patients’ retention in HIV chronic care facilities. The study recommends that HIV programmes take a holistic approach in tackling problems associated with patients’ retention in HIV chronic care clinics. In this regard, employees should be given days off to attend their appointments, the government ought to decentralise HIV services to the lowest level, and further offer attitude trainings to HIV chronic care providers.